1992
DOI: 10.1080/15287399209531611
|View full text |Cite
|
Sign up to set email alerts
|

Removal of toxic metals and nonmetals from contaminated water

Abstract: The effects of the application of potassium ferrate to remove possible toxic compounds are presented. Potassium ferrate (K2FeO4) is shown in this work to be an effective means to remove toxic metals and nonmetals from aqueous solution. The toxic material present in water is precipitated from aqueous solution and readily removed. Potassium ferrate removes itself from solution. Discolored contaminated water may be made clear by utilizing potassium ferrate. In addition, turbidities of solutions induced by dissolv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
4

Year Published

1993
1993
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 3 publications
0
29
0
4
Order By: Relevance
“…Potassium ferrate can also remove a range of metals (e.g., Mn 2+ , Cu 2+ , Pb 2+ , Cd 2+ , Cr 3+ , and Hg 2+ ) to a low level at a dose range of 10-100 mg/l as K 2 FeO 4 by oxidation and co-precipitation [35]. Arsenic(III) oxidation efficiency with ferrate(VI) was examined recently [36].…”
Section: Oxidation Of Inorganic Pollutantsmentioning
confidence: 99%
“…Potassium ferrate can also remove a range of metals (e.g., Mn 2+ , Cu 2+ , Pb 2+ , Cd 2+ , Cr 3+ , and Hg 2+ ) to a low level at a dose range of 10-100 mg/l as K 2 FeO 4 by oxidation and co-precipitation [35]. Arsenic(III) oxidation efficiency with ferrate(VI) was examined recently [36].…”
Section: Oxidation Of Inorganic Pollutantsmentioning
confidence: 99%
“…More importantly, ferrate(VI) is also an environmental friendly treatment chemical, which will not produce any harmful by-products in the treatment process. Previous studies have shown that potassium ferrate (VI) can perform superiorly in degrading various synthetic and natural organic pollutants (Bartzatt and Carr, 1986;Sharma and Bielski, 1991;Bielski et al, 1994;Norcross et al, 1997;Gulyas, 1997;White and Franklin, 1998;Sharma, 2002;Jiang and Wang, 2003a), inactivating harmful microorganisms (Murmann and Robinson, 1974;Gilbert et al, 1976;Schink and Waite, 1980;Kazama, 1995;Jiang and Wang, 2003b), and coagulating colloidal particles and heavy metals (Bartzatt et al, 1992;Jiang et al, 2001;Jiang, 2003).…”
Section: Introductionmentioning
confidence: 98%
“…It has been reported that heavy metals such as Mn 2+ , Cu 2+ , Pb 2+ , Cd 2+ , Cr 3+ , and Hg 2+ could be effectively removed using potassium ferrate(VI) through oxidation and coagulation (Bartzatt et al 1992;Lim and Kim 2009a). In addition, ferrate(VI) was effective in the oxidation of As(III) into As(V), which could be removed through adsorption onto Fe(OH) 3 (Fan et al 2002;Lee et al 2003;Jain et al 2009;Sharma and Sohn 2009).…”
Section: Introductionmentioning
confidence: 99%